Hoxa10 Dna Methylation Level In The Endometrium Women With Endometriosis: A Systematic Review - Marjanu Hikmah Binti Elias; Nurunnajah Lazim; Zulazmi Bin Sutaji; Mohammad Azrai Abu; Abdul Kadir Abdul Karim; Azizah Ugusman; Saiful Effendi Syafruddin; Mohd Helmy Mokhtar; Mohd Faizal Ahmad (MDPI, 2024)
Indexed by WOS/Scopus/ERA